Pencegahan Wabah Penyakit Kaki, Tangan dan Mulut, Cacar monyet, dan Hepatitis Misterius - Kharisma, Dayu Swasti; Syahniar, Rike; Rayhana, Rayhana; Latifah, Noor; Ferdiansyah, Ferry; Fauzia, Ghina Zahrotul (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
The emergence of various outbreaks in the midst of the ongoing Covid-19 pandemic is quite worrying. Among them are mysterious hepatitis, Hand Mouth and Foot Disease (HMFD), and monkeypox, also known as monkeypox. This is the main reason for the importance of the public to know valid information about infectious diseases and how to prevent them. One of the efforts to increase public knowledge is to conduct counseling and assistance on a regular basis, with the hope of increasing public awareness so as to reduce transmission rates. Counseling was carried out with material on introduction to outbreaks of acute hepatitis, monkeypox and HMFD accompanied by Clean and Healthy Living Behavior for prevention and taught how to wash hands in the right way, and how to wear the mask correctly. 76.4% of respondents were satisfied with this counseling activity. There was an increase in the mean value of the participants knowledge before and after counseling, with the mean + SD pre and post test values respectively 84.4 ± 19.7 and 85 ± 21. There was no statistically difference knowledge before and after counseling with a p-value of 0.728.